Therapeutic isolation and expansion of human skeletal muscle-derived stem cells for the use of muscle-nerve-blood vessel reconstitution - Tamaki, Tetsuro; Uchiyama, Yoshiyasu; Hirata, Maki; Hashimoto, Hiroyuki; Nakajima, Nobuyuki; Saito, Kosuke; Terachi, Toshiro; Mochida, Joji (Frontiers in Physiology, 2015)
Skeletal muscle makes up 40-50% of body mass, and is thus considered to be a good adult stem cell source for autologous therapy. Although, several stem/progenitor cells have been fractionated from mouse skeletal muscle showing a high potential for therapeutic use, it is unclear whether this is the case in human. Differentiation and therapeutic potential of human skeletal muscle-derived cells (Sk-Cs) was examined. Samples (5-10 g) were obtained from the abdominal and leg muscles of 36 patients (age, 17-79 years) undergoing prostate cancer treatment or leg amputation surgery. All patients gave informed consent. Sk-Cs were isolated using conditioned collagenase solution, and were then sorted as CD34-/CD45-/CD29+ (Sk-DN/29+) and CD34+/CD45- (Sk-34) cells, in a similar manner as for the previous mouse Sk-Cs. Both cell fractions were appropriately expanded using conditioned culture medium for about 2 weeks. Differentiation potentials were then examined during cell culture and in vivo transplantation into the severely damaged muscles of athymic nude mice and rats. Interestingly, these two cell fractions could be divided into highly myogenic (Sk-DN/29+) and multipotent stem cell (Sk-34) fractions, in contrast to mouse Sk-Cs, which showed comparable capacities in both cells. At 6 weeks after the separate transplantation of both cell fractions, the former showed an active contribution to muscle fiber regeneration, but the latter showed vigorous engraftment to the interstitium associated with differentiation into Schwann cells, perineurial/endoneurial cells, and vascular endothelial cells and pericytes, which corresponded to previous observations with mouse SK-Cs. Importantly, mixed cultures of both cells resulted the reduction of tissue reconstitution capacities in vivo, whereas co-transplantation after separate expansion showed favorable results. Therefore, human Sk-Cs are potentially applicable to therapeutic autografts and show multiple differentiation potential in vivo.